2021
DOI: 10.1044/2021_persp-21-00107
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and Social Isolation in Older Adults: The Effects of a Pandemic

Abstract: Purpose: This clinical focus article examines the effect of social isolation and loneliness forced by the pandemic on the geriatric population. Since March 11, 2020, when a global pandemic was declared, a new concept of social distancing has swept the United States and the world. While these efforts have been challenging for the entire population, there has been a disproportionate effect on minority groups, low-income communities, and one especially vulnerable group that has emerged: older adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…A national survey from Cigna reported that all ages may experience social isolation and loneliness [7]. The findings also corresponded to the prior literature showing high loneliness and/isolation and stress among older adults [3,29], as well as among young adults [8,9] during COVID-19. In addition, our study found that the Bigs experienced slightly higher levels of loneliness than the Minis.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A national survey from Cigna reported that all ages may experience social isolation and loneliness [7]. The findings also corresponded to the prior literature showing high loneliness and/isolation and stress among older adults [3,29], as well as among young adults [8,9] during COVID-19. In addition, our study found that the Bigs experienced slightly higher levels of loneliness than the Minis.…”
Section: Discussionsupporting
confidence: 81%
“…During COVID-19, prolonged periods of social distancing may result in negative effects for older adults long after quarantining ends [2]. Overall, older adults are at higher risk for contracting COVID-19 and reported feeling isolated, lonely, and stressed as the pandemic progressed [3].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically in geriatrics, the loneliness which accompanied social isolation was associated with multiple negative effects, including declining mental and physical health, increased suicidal ideation and attempts, as well as anxiety, fear, and increased risk of substance abuse. 3 Specifically regarding alcohol use, increased risk of harmful alcohol use and alcohol dependence has been demonstrated, especially in those with mental health symptomology. 4 With the practice of alcohol screening required at verified trauma centers, this may provide us a needed opportunity to identify these at-risk individuals.…”
mentioning
confidence: 99%
“…Among colleagues there have been interactive online events, such as virtual scavenger hunts, trivia competitions, and cook-alongs. Online gaming has shown to influence offline social support positively (Trepte et al, 2012), while outdoor activities performed at physical distance, such as yard work or picnics may be appropriate tools to foster social contacts for the elderly (Heape, 2021). Although, there are ideas to overcome negative effects of social isolation, there is much need to evaluate the effectiveness of existing ideas, and design new measures based on scientific research.…”
Section: Knowledge Gained and Implicationsmentioning
confidence: 99%